The Traditional jewelry of Egypt - Fahmy, Azza,
In this illustrated book, Azza Fahmy, a world-renowned designer of jewelry based on traditional motifs, lays before us an Aladdin's cave of jewelry made in all corners of Egypt over the last one hundred years, collected through her extensive travels throughout the country.